PENGARUH TEMPERATUR DAN KELEMBABAN TERHADAP TINGKAT KERUSAKAN DAUN JABON ( Anthocephalus cadamba ) OLEH Arthrochista hilaralis - Pribadi, Avry; Anggraeni, Illa (Jurnal Penelitian Hutan Tanaman, 2011)
ABSTRACTArthrochista hilaralisÂ is the defoliator pest that caused foliar damage (severity level) up to 97,88% onjabon plantation at HTI Baserah sector and 67,80% at Pantai Cermin community forest. The difference ofseverity level between these location is probably caused by temperature and humidity. The aim of thisresearch was to find the role of temperature and humidity to foliar damage caused by A. hilaralis.Systematic sampling was used to determined the observation plot. There were 5 plots and every plotcontain 100 trees. Observation was done to foliar severity level and abiotic factor (temperature andhumidity). The results show that the temperature has negative correlation (-0,288**) and humidity haspositive correlation (0,303**) to severity level at HTI Baserah but at HR Pantai Cermin showed thattemperature has positive correlation (0,169**) and humidity has negative correlation (-0,187**). Theregression equation between severity level to temperature and humidity at HTI Baserah sector was Y=4,418 â 0,015X1 + 0,014X2 (R= 0,305) and Y= 4,961 0,029X1 0,004X2 (R= 0,187) at HR PantaiCermin.